2018
DOI: 10.1002/ajpa.23475
|View full text |Cite
|
Sign up to set email alerts
|

Ancient DNA reveals temporal population structure within the South‐Central Andes area

Abstract: Population structure in South America has been mostly studied on current native groups, mainly showing a west-to-east differentiation between the Andean and lowland regions. Here we demonstrated that genetic population differentiation preceded the European contact and might have been more complex than thought, being found within the South-central Andes Area. Moreover, divergence among temporally different populations might be reflecting socio-political changes occurred in the evermore complex pre-Hispanic Ande… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 51 publications
0
5
0
Order By: Relevance
“…Archaeological research in the Central Andes is extraordinarily rich ( Silverman and Isbell, 2008 ), but ancient DNA (aDNA) studies to date have been limited, so there has been little information about demographic change over time. Studies of uniparental DNA indicated evidence for a degree of genetic homogeneity of the Central and Southern Highlands, especially for the Y chromosome ( Barbieri et al., 2014 , Gómez-Carballa et al., 2018 , Harris et al., 2018 , Sandoval et al., 2013 , Sandoval et al., 2016 ), while studies with aDNA suggested substantial continuity as well as gene flow between the Coast and the Highlands ( Baca et al., 2012 , Fehren-Schmitz et al., 2014 , Fehren-Schmitz et al., 2017 , Llamas et al., 2016 , Russo et al., 2018 , Valverde et al., 2016 ). High coverage genome-wide ancient DNA data from South America from the time before European contact began to be published in 2018, with most data from mid- to early-Holocene hunter-gatherers (in the Central and South-Central Andes, 23 individuals were reported) ( Lindo et al., 2018 , Moreno-Mayar et al., 2018b , Posth et al., 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…Archaeological research in the Central Andes is extraordinarily rich ( Silverman and Isbell, 2008 ), but ancient DNA (aDNA) studies to date have been limited, so there has been little information about demographic change over time. Studies of uniparental DNA indicated evidence for a degree of genetic homogeneity of the Central and Southern Highlands, especially for the Y chromosome ( Barbieri et al., 2014 , Gómez-Carballa et al., 2018 , Harris et al., 2018 , Sandoval et al., 2013 , Sandoval et al., 2016 ), while studies with aDNA suggested substantial continuity as well as gene flow between the Coast and the Highlands ( Baca et al., 2012 , Fehren-Schmitz et al., 2014 , Fehren-Schmitz et al., 2017 , Llamas et al., 2016 , Russo et al., 2018 , Valverde et al., 2016 ). High coverage genome-wide ancient DNA data from South America from the time before European contact began to be published in 2018, with most data from mid- to early-Holocene hunter-gatherers (in the Central and South-Central Andes, 23 individuals were reported) ( Lindo et al., 2018 , Moreno-Mayar et al., 2018b , Posth et al., 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…Another question we introduced was whether the horticultural groups described by the early colonizers' chronicles replaced the ancient hunter‐gatherer populations or if, instead, there was a biological continuity over time accompanied by a local cultural development. The high incidence of Hg B in Sierras in the post 1200 yBP subsample (44%, Table 2) was interpreted in a previous work (Nores et al, 2011) as a signal of gene flow into the Sierras region from populations with high incidence of Hg B, such as the South‐Central Andean region, including modern day Perú, Northern Chile and Northwestern Argentina (Russo, Mendisco, et al, 2018), or the Gran Chaco region (Demarchi et al, 2001). However, our analysis of mtDNA haplogroups and HVR‐I sequences does not support this hypothesis, since no genetic structure was observed between temporal subsets.…”
Section: Discussionmentioning
confidence: 76%
“…The HVR‐I sequences from the Plains and Sierras samples were compared with other ancient groups from Argentina to investigate their affinities (references in Supplementary Table 3). Sequences from different archeological sites and chronologies were grouped together based on their geographical proximity (Figure 1), except for the Los Amarillos site, located in Quebrada de Humahuaca, which was considered as a separate population given its relatively large sample size and its unusually high incidence of haplogroup (Hg) A2 (Mendisco et al, 2011; Russo, Mendisco, et al, 2018). The ancient data were also compared with those of contemporary individuals with Native American lineages from small, semi‐rural populations of Central Argentina (García et al, 2018; Pauro et al, 2013) to check for population continuity up to the present (Supplementary Table 3).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…For the following Late or Regional Developments Period (RDP) (ca. AD 1000-1450), seven studies were carried out on samples from different regions of NWA: Quebrada de Humahuaca (Mendisco et al 2011(Mendisco et al , 2014(Mendisco et al , 2018Russo et al 2016Russo et al , 2018aRusso et al , 2018b, the Northern Calchaquí Valleys (Mendisco et al 2014), and the Puna highlands of Jujuy Province (Mendisco et al 2014;Postillone et al 2017). For the subsequent Inca Period (ca.…”
mentioning
confidence: 99%